Job Vacancies, the Beveridge Curve, and Supply Shocks: The Frequency and Content of Help-Wanted Ads in Pre- and Post-Mariel Miami - Jason Anastasopoulos; George J. Borjas; Gavin G. Cook; Michael Lachanski (Institute of Labor Economics (IZA), 2019)
Beginning in 1951, the Conference Board constructed a monthly job vacancy index by counting the number of help-wanted ads published in local newspapers in 51 metropolitan areas. We use the Help-Wanted Index (HWI) to document how immigration changes the number of job vacancies in the affected labor markets. Our analysis revisits the Mariel episode. The data reveal a marked drop in Miami's HWI relative to many alternative control groups in the first 4 or 5 years after Mariel, followed by recovery afterwards. The Miami evidence is consistent with the observed relation between immigration and the HWI across all metropolitan areas in the 1970- 2000 period: these spatial correlations suggest that more immigration reduces the number of job vacancies. We also explore some of the macro implications of the Mariel supply shock and show that Miami's Beveridge curve shifted inwards by the mid-1980s, suggesting a more efficient labor market, in contrast to the outward nationwide shift coincident with the onset of the 1980- 1982 recession. Finally, we examine the text of the help-wanted ads published in a number of newspapers and document a statistically and economically significant post-Mariel decline in the relative number of low-skill vacancies advertised in the Miami Herald.
Keywords: J23; J6; 330; job vacancies; immigration; Beveridge Curve